2016
DOI: 10.14202/vetworld.2016.888-892
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and pathogenesis of some filarial nematodes infecting donkeys in Egypt

Abstract: Aim:The primary objective of the present study is to determine the commonness of filarial parasites in donkeys in Egypt, identification of the filarial species tainting them and the delivered pathogenic impact connected with the infestation.Materials and Methods:A total of 188 donkeys were examined for filarial infection. The blood samples and scraping of the cutaneous bleeding lesions were collected, stained, and inspected for microfilariae all through the period from March 2011 to October 2013. The adult wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 11 publications
1
23
0
Order By: Relevance
“…In previous studies, when the occurrence of O. cervicalis and O. reticulata was investigated concurrently, O. cervicalis was more prevalent than O. reticulata. In fact, prevalence values of 82.98 and 4.26% have been reported for O. cervicalis and O. reticulata in donkeys, respectively (13). Similarly, prevalence values of 25.42, 5.93, and 2.54% have been reported for O. cervicalis, O. reticulata, or both infections in horses, respectively (14).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In previous studies, when the occurrence of O. cervicalis and O. reticulata was investigated concurrently, O. cervicalis was more prevalent than O. reticulata. In fact, prevalence values of 82.98 and 4.26% have been reported for O. cervicalis and O. reticulata in donkeys, respectively (13). Similarly, prevalence values of 25.42, 5.93, and 2.54% have been reported for O. cervicalis, O. reticulata, or both infections in horses, respectively (14).…”
Section: Discussionmentioning
confidence: 98%
“…There have been few epidemiological studies on Onchocerca infection in donkeys. Reported prevalence values are 65.38% (21) and 82.98% (13) for O. cervicalis in Egypt, 34% for O. raillieti in Sudan (10), and 4.26% for O. reticulata in again Egypt (13). In another study, only one donkey was examined and found to be infected with O. cervicalis (22).…”
Section: Discussionmentioning
confidence: 99%
“…Adult S equina is a filarial parasite commonly found floating free within the peritoneal cavity of the equines . Worldwide, the parasite was distributed through the mosquito vectors …”
Section: Introductionmentioning
confidence: 99%
“…Among the most common surgical conditions of equine ocular setariasis is a vision threatening disease of equine resulting from ectopic parasitism caused by Setaria spp, a genus of filaroid worms (Gangwar et al, 2008;Radwan et al, 2016). In India equine ocular setariosis, an important cause of corneal opacity is commonly caused by Setaria digitata, Setaria equina and Thelazia lacrymalis (Sathu, 1974;Ladoucer & Kazacos, 1981;Parrah et al, 2004;Sellon & Long, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The parasite exhibits migratory behavior in unusual hosts such as horses, donkeys or human beings and can be found in various organs such as heart, lung, spleen, kidney, uterus, oviduct, ovary, and urinary bladder (Varma et al, 1971). All equines are generally more prone for ocular worm (Pratap, et al, 2005;Jayakumar et al, 2012;Radwan et al, 2016).The immature worm can also invade eye (Sreedevi et al, 2002;Tuntivanich et al, 2011) through the vascular system (Townsend, 2013). The eye infection occurs when the adult worm meanders through intraocular tissue, thus it is also called as eye worm.…”
Section: Introductionmentioning
confidence: 99%